Royal Art and the State of Czech Medieval Art History Studies as of 2010 - Bartlová, Milena (Dějiny – teorie – kritika, 2010)
2010 saw the publication of two sizable volumes containing many years of work by prominent Czech medievalists – JIŘÍ KUTHAN, The Royal Work under George of Poděbrady and the Jagellon Dynasty; KLÁRA BENEŠOVSKÁ (ed.), The Royal Wedding 1310 (Prague City Gallery exhibition catalogue). After a recapitulation of the contents of both books the procedural methodology of both researchers (or the editors and their chief co-workers in the case of the exhibition catalogue) comes under criticism. It turns out that both share a similar approach involving their specifi c treatment of literature and particularly their antiquated method of working with historical sources. The most critical element involves their lack of attention to more recent historiographical literature and ignorance of basic approaches to cultural history. These features are shared by a considerable segment of Czech medieval art history studies.